2008
DOI: 10.1016/j.bbmt.2008.01.006
|View full text |Cite
|
Sign up to set email alerts
|

Systemic Administration of Multipotent Mesenchymal Stromal Cells Reverts Hyperglycemia and Prevents Nephropathy in Type 1 Diabetic Mice

Abstract: Multipotent mesenchymal stromal cells (MSCs), often labeled mesenchymal stem cells, contribute to tissue regeneration in injured bone and cartilage, as well as in the infarcted heart, brain, and kidney. We hypothesize that MSCs might also contribute to pancreas and kidney regeneration in diabetic individuals. Therefore, in streptozotocin (STZ)-induced type 1 diabetes C57BL/6 mice, we tested whether a single intravenous dose of MSCs led to recovery of pancreatic and renal function and structure. When hyperglyce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
254
6
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 304 publications
(272 citation statements)
references
References 42 publications
11
254
6
1
Order By: Relevance
“…While hess et al [51] reported marked reduction of serum glucose occur as early as 4 days after transplantation of bone marrow derived cells into STZtreated mice due to stimulation of endogenous cells to proliferate and produce insulin. In accordance with our study, some evidences reported that single infusion of MSCs decrease blood glucose in STZ diabetic rats [52], [53]. Dong et al [52] reported that MSCs homed to pancreas of recipient rats and transdifferentiated into insulin-producing cells.…”
Section: Discussionsupporting
confidence: 92%
“…While hess et al [51] reported marked reduction of serum glucose occur as early as 4 days after transplantation of bone marrow derived cells into STZtreated mice due to stimulation of endogenous cells to proliferate and produce insulin. In accordance with our study, some evidences reported that single infusion of MSCs decrease blood glucose in STZ diabetic rats [52], [53]. Dong et al [52] reported that MSCs homed to pancreas of recipient rats and transdifferentiated into insulin-producing cells.…”
Section: Discussionsupporting
confidence: 92%
“…Although their immunomodulatory properties are not yet completely understood, their low immunogenic potential, together with their effects on immune responses, make them a promising therapeutic tool for severe refractory autoimmune diseases. MSCs have already been used in clinical trials as a treatment for acute graft-versus-host disease following allogeneic HSCT (25,26) and for autoimmune diseases such as systemic sclerosis (27) and type 1 diabetes mellitus (28).…”
Section: Discussionmentioning
confidence: 99%
“…MSCs have been applied for the repair of arthritis [63], cardiac muscle [152,153], lung tissue [150], diabetes [154], skin [81,83,155,156], skeletal tissue [157], and digestive tract tissue [87,148,158]. …”
Section: Mesenchymal Stromal Cells (Mscs) Clinical Trials In Various mentioning
confidence: 99%